2010
DOI: 10.1021/ja9093617
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a Radiolabeled Cluster Inside a Fullerene Cage, 177LuxLu(3−x)N@C80: An Interleukin-13-Conjugated Radiolabeled Metallofullerene Platform

Abstract: In this communication, we describe the successful encapsulation of (177)Lu into the endohedral metallofullerene (177)Lu(x)Lu(3-x)N@C(80) (x = 1-3) starting with (177)LuCl(3) in a modified quartz Kraschmer-Huffman electric generator. We demonstrate that the (177)Lu (beta-emitter) in this fullerene cage is not significantly released for a period of up to at least one-half-life (6.7 days). We also demonstrate that this agent can be conjugated with an interleukin-13 peptide that is designed to target an overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 16 publications
4
117
1
Order By: Relevance
“…[5] Radioisotope 177 Lu has favorably long nuclear decay properties (t 1/2 = 6.65 d) and can be used to easily radiolabel av ariety of molecular carriers. [6] As such, 177 Lu promises to benefit nanoparticle-mediated combination therapy.Previous studies explored 177 Lu-labeled gold nanoparticles for preclinical nuclear medicine. [7] However,t he clinical translation of the reported nanosystem was impeded because of high and long-term accumulation in the reticuloendothelial system (RES) and low intratumor uptake.T hus,i tr emains ab ig challenge to integrate nanocarrier tumor-targeted delivery and multi-modal imaging using 177 Lu to obtain an anotheranostic agent with high efficiacy.…”
mentioning
confidence: 99%
“…[5] Radioisotope 177 Lu has favorably long nuclear decay properties (t 1/2 = 6.65 d) and can be used to easily radiolabel av ariety of molecular carriers. [6] As such, 177 Lu promises to benefit nanoparticle-mediated combination therapy.Previous studies explored 177 Lu-labeled gold nanoparticles for preclinical nuclear medicine. [7] However,t he clinical translation of the reported nanosystem was impeded because of high and long-term accumulation in the reticuloendothelial system (RES) and low intratumor uptake.T hus,i tr emains ab ig challenge to integrate nanocarrier tumor-targeted delivery and multi-modal imaging using 177 Lu to obtain an anotheranostic agent with high efficiacy.…”
mentioning
confidence: 99%
“…28). 164 The encapsulated 177 Lu(III) ions were not released for at least one half-life (6.7 177-Lu x Lu 3-x N@C 80 surface functionalisation for solubility, biocompatibility and targeting days) showing the robustness of the system, and the fullerene was surface tagged with an interleukin-13 peptide. The mechanism for the loss of 177 Lu from the cage beyond this timescale has not been postulated, but assumed to proceed via radiolytic damage.…”
Section: Complexes For Radioimmunotherapy Applicationsmentioning
confidence: 99%
“…For the imaging capabilities of this theranostic agent, see Ref. 327. Regarding therapeutic efficacy in vivo, see Ref.…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%
“…346 It was also shown that a conjugate of radiolabelled cluster 177 Lu x Lu (37x) N@C 80 with the 1L-13 peptide and a fluorescent tag (tetramethyl-6-carboxyrhodamine, TAMRA) can be used for radiotherapeutic and radiodiagnostic applications. 327 Endometallofullerenes and chemotherapeutic pharmaceuticals. Anticancer drugs can also be designed on the basis of EMFs containing no radioactive atoms.…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%